PENINGKATAN KUALITAS PEMBELAJARAN KEAKSARAAN DASAR (FUNCTIONAL LITERACY) MELALUI PENDEKATAN KONSTRUKTIVISTIK DI SKB JAKARTA TIMUR - untung untung; Latang Latang; Fatmawati Gaffar (UNIVERSITAS NEGERI MAKASSAR, 2024)
The aim of this research is to improve the quality of functional literacy learning through a constructivist approach related to students' mastery of competencies, namely reading, writing, arithmetic and communicating in Indonesian. This action research was carried out in the functional literacy learning group